Odpowiedzi

2010-02-02T21:02:32+01:00
X + y = 20 / (-2) m. przeciwnych współczynników
2x + 3y = 52

-2x -2y = -40
2x + 3y = 52
y = 12
x = 20 -12 = 8


2x + y =16 / (-6)
5x - 6y =0
-12x -6y = -96
5x - 6y =0
-7x = - 96 / : (-7)
x = 13 5/7
y = 16 - 2 *13 5/7 = 16 - 27 3/7 = - 11 3/7
9 4 9
2010-02-02T21:03:04+01:00
A)x + y = 20
2x + 3y = 52

Z pierwszego równania:
x = 20 - y
Podstawiam do drugiego:
2*(20-y) + 3y = 52
40-2y+3y=52
y=12
Wyliczam x:
x = 20-12 = 8

b) 2x + y =16
5x - 6y =0

Z pierwszego równania:
2x = 16 - y
x = 8 - 1/2y
Podstawiam do drugiego:
5*(8 - 1/2y) - 6y = 0
40-2,5y-6y=0
-8,5y=-40
y = 80/17
Wyliczam x:
x = 8-1/2y = 96/17
6 2 6
2010-02-02T21:05:56+01:00
A)
x+y=20 / * (-2)
2x+3y=52

-2x-2y=-40
2x+3y=52
y=12

x+y=20 / *(-3)
2x+3y=52

-3x-3y=-60
2x+3y=52
-x=-8 /:(-1)
x=8

b)
2x + y =16 / *(-5)
5x - 6y =0 / *2

-10x -5y=-80
10x-12y=0
-17y=-80 /:-17
y=80/17

2x + y =16 / /*6
5x - 6y =0

12x+6y=96
5x-6y=0
17x=96/"17
x=96/17
8 4 8